Maskot Sebagai Representasi Identitas Visual Grup K-Pop: Studi Kasus dan Eksplorasi Konsep Maskot Enhypen - Budisartono, Elvira; Fuad, Ahmad (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2025)
In the K-Pop industry, mascots are one of the most effective visual media for strengthening a group's identity and building a connection with fans. However, not all groups have official mascots, including ENHYPEN, which is known for its strong visual concept. This study aims to explore the possibility of designing an ENHYPEN mascot based on the group's visual elements and fan preferences. The method used is a mixed method, including observation of fan-made characters, online questionnaire distribution, and interviews. The collected data includes audience preferences for visual styles such as eye shape, color, body proportions, and symbolic elements associated with each member. This study focuses on how these elements can be analyzed and interpreted in the context of mascot character design as part of a K-Pop group's visual identity strategy.